Justice Delayed, Justice Denied: A Critical Examination of Repeated Suspect Status in Indonesia - Susilo, Erwin; Din, Mohd.; Suhaimi, Suhaimi; Mansur, Teuku Muttaqin (Faculty of Law, Hasanuddin University, 2024)
The Indonesian criminal justice system faces critical issues with the repeated designation of individuals as suspects, which compromises legal certainty and the protection of human rights. This study provides a critical analysis of the procedural and ethical consequences of repeated suspect designations within the framework of Indonesia's Criminal Procedure Code. This study employs a doctrinal legal research methodology, incorporating statute, case and conceptual approaches. The results show that pretrial judges assess the validity of suspect designations based on procedural and formal principles. Their authority is confined to reviewing formal aspects. These limitations underscore that pretrial proceedings focus solely on administrative and procedural compliance rather than the substantive merits of the case. This formalist perspective follows civil procedural principles, emphasizing procedural correctness over material truth. While pretrial judges can annul a suspect designation, investigators can re-designate the person as a suspect if new evidence is presented. Such a reform would ensure a more balanced relationship between judicial oversight and investigative authority, minimizing arbitrary practices and enhancing procedural fairness. However, the recurring practice of re-designating suspects raises a significant flaw in the system, undermining legal certainty and eroding public trust.